The Analysis Of Factors Affect The Quality Of Competitive Strategy In Industry SME For Embroidery At Padang City (JURNAL ECONOMICA : Research of Economic And Economic Education, 2016)
Dahliana Kamener, Helmawati,Economic Faculty,  Bung Hatta University,By Pass Street, Aie Pacah, Padang, Sumatera BaratEmail Address: dahlianakamener@ymail.comPhone No.: +628126603075 (mobile) ABSTRACTThe study aimed to analyze the quality factors of competitive strategy on SME for Industrial embroidery  in Padang city. With this research is expected to provide benefits to the industry, especially SMEs Industrial embroidery to be able to improve and consider the factors that can affect the quality of competitive strategy in this industry, which the factors influenced such as Quality Strategic Asset, Environment Adabtability and price strategic to the Quality Strategic Competition. The populations of this study were SME industry for the embroidery product in the city of Padang and used  census sampling. Data retrieved from the primary data by spreading questionnaires and the measurement by using a Likert scale. Methods of analysis by using descriptive analysis, multiple regression analysis to test the hyphotheses. The result showed that the quality of asset strategik was postively significant effect the Quality Strategic Competition, and enviromental adaptability and price strategy have positively not significant effect on the Quality Strategic Competition.